Arabidopsis KAM2/GRV2 Is Required for Proper Endosome Formation and Functions in Vacuolar Sorting and Determination of the Embryo Growth Axis - Tamura, Kentaro (American Society of Plant Biologists, 2007)
We isolated an Arabidopsis thaliana mutant, katamari2 (kam2), that has a defect in the organization of endomembranes. This mutant had deformed endosomes and formed abnormally large aggregates with various organelles. Map-based cloning revealed that kam2 is allelic to gravitropism defective 2 (grv2). The KAM2/GRV2 gene encodes a homolog of a DnaJ domain–containing RECEPTOR-MEDIATED ENDOCYTOSIS-8, which is considered to play a vital role in the endocytotic pathway from the plasma membrane to lysosomes in animal cells. Immunofluorescent staining showed that KAM2/GRV2 protein localizes on punctate structures, which did not merge with any markers for Golgi, trans-Golgi network, endosomes, or prevacuolar compartments. KAM2/GRV2, which does not have a predicted transmembrane domain, was peripherally associated with the membrane surface of uncharacterized compartments. KAM2/GRV2 was expressed at the early to middle stages of seed maturation. We found kam2 mis-sorted seed storage proteins by secreting them from cells, indicating that KAM2/GRV2 is involved in the transport of the proteins into protein storage vacuoles. kam2 had another defect in embryogenesis. Half of the developing kam2-1 cotyledons grew into the opposite space of the seeds before the walking stick–shaped embryo stage. Our findings suggest that KAM2/GRV2 is required for proper formation of the endosomes involving protein trafficking to the vacuoles and determination of growth axis of the embryo.